Thermal degradation studies of alkyl-imidazolium salts and their application in nanocomposites - Awad, W.H.; Gilman, J.W.; Nydena, M.; Harris, R.H.Jr.; Sutto, T.E.; Callahan, J.; Trulove, P.C.; Trulove, P.C.; Fox, D.M.
of polymer-layered silicate nanocomposites on the industrial scale. To circumvent the detrimental effect of the lower thermal stability of alkyl ammonium-treated montmorillonite, a series of alkyl-imidazolium molten salts were prepared and characterized by elemental analysis, thermogravimetry (TGA)and thermal desorption mass spectroscopy (TDMS). The effect of counter ion, alkyl chain length and structural isomerism on the thermal stability of the imidazolium salts was investigated. Alkyl-imidazolium-treated montmorillonite clays were prepared by ion exchange of the imidazolium salts with Na-montmorillonite. These organically-modified clays were characterized by X-ray diffraction (XRD), TDMS and thermogravimetry coupled with Fourier transform infrared spectroscopy (TGA-FTIR), and compared to the conventional quaternary alkyl ammonium montmorillonite. Results indicate that the counter ion has an effect on the thermal stability of the imidazolium salts, and that imidazolium salts with PF6-, N(SO2CF3)2- and BF4- anions are thermally more stable than the halide salts. A relationship was observed between the chain length of the alkyl group and the thermo-oxidative stability; as the chain length increased from propyl, butyl, decyl, hexadecyl, octadecyl to eicosyl, the stability decreased. The results also show that the imidazolium-treated montmorillonite has greater thermal stability compared to the imidazolium halide. Analysis of the decomposition products by FTIR provides an insight about the decomposition products which are water, carbon dioxide and hydrocarbons.
Keywords: IMIDAZOLIUM SALTS; MONTMORILLONITE; NANOCOMPOSITE; THERMAL STABILITY; DEGRADATION